Augmented reality learning environment for physiotherapy education. (2nd January 2018) - Kelly, David; Hoang, Thuong N.; Reinoso, Martin; Joukhadar, Zaher; Clements, Tamara; Vetere, Frank
Abstract : Background: An understanding of how to translate anatomical knowledge and application of body mechanics to dynamic scenarios with real-life clients and movement is often a challenge for physiotherapy students. Objective: Augmented Studio is an augmented reality system that helps facilitate this by projecting anatomical structures over moving bodies and allowing annotation of these structures. Methods: Via a user and learner-centred design approach, augmented reality technology can assist education of physiotherapy students through augmentation and annotation. Results: Using projection mapping Augmented Studio enables display of anatomy such as skeleton and muscles on the body in real time as it moves. With the creation of a technique to deliver hand-drawing annotation projected onto the moving body student and teacher clinical reasoning strategies can be made explicit. Conclusion: Outcomes from a pilot usability study showed that Augmented Studio promotes the creation of an engaging teaching and learning experience and the facilitation of communication between teachers and students.